Pengaruh Kompensasi terhadap Kinerja Pegawai PT Transportasi Jakarta - Fauzi, Achmad; Rustomo, Rustomo; Lelisa, Widya (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This article discusses the influence of compensation on employee performance at PT Transportasi jakarta. This research aims to determine whether compensation has an impact on employee performance. The research methodology employed is quantitative, and data were collected through a questionnaire. The validity and reliability of the questionnaire were tested, and the data were analyzed using IBM SPSS Statistics 26. The research results indicate that compensation has a significant influence on employee performance. This article emphasizes the importance of fair compensation in motivating employees and enhancing their job satisfaction. The research findings demonstrate that every one-unit increase in compensation will increase employee performance by 25.7%. However, there are other factors that also affect employee performance by 69.9%. Therefore, companies need to consider other factors such as motivation, work environment, and skills in improving employee performance. This research provides a better understanding of the importance of fair compensation in creating a motivating work environment and improving employee job satisfaction. The practical implications of this research are that companies should pay attention to the compensation provided to their employees to ensure that they feel valued and motivated to deliver their best performance.